Malaysia’s branding as an Islamic tourism hub: an assessment - Fatemeh Shafaei,; Badaruddin Mohamed, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Malaysia is attempting to be a popular Islamic tourist destination in the world owing to its Islamic environment. It is already noted as an Islamic country serious in establishing a halal hub for financial products as well as services. As a further step forward it is embracing novel concepts such as Islamic and halal tourism in recent years. While the country does have the potentials of advancing Islamic tourism and hospitality industry with respect to the arts, heritage and unique culture of the Malay Muslims, the evaluation of such strategic branding efforts has rarely been attempted. This study outlines Malaysia’s marketing efforts in branding itself as an Islamic tourism hub. A SWOT analysis was conducted to summarize the country’s internal (strengths and weaknesses) and external (opportunities and threats) issues in branding itself as an Islamic destination.